2022
DOI: 10.3390/nu14071438
|View full text |Cite
|
Sign up to set email alerts
|

Aging-Related Behavioral, Adiposity, and Glucose Impairments and Their Association following Prenatal Alcohol Exposure in the C57BL/6J Mouse

Abstract: People that experience prenatal alcohol exposure (PAE) may have behavioral and metabolic impairments, and it is unclear whether these remain stable or change with age. We assessed behavioral and metabolic endpoints across the lifespan in a mouse model of fetal alcohol spectrum disorder (FASD). Pregnant C57BL/6J mice received alcohol (ALC; 3 g/kg) or maltose-dextrin (control, CON) daily from embryonic day 8.5 to 17.5. Offspring were tested on accelerating rotarod, Y-maze, novel object recognition, and fear cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…This is consistent with previous studies using targeted deletion of LRP1 in the forebrain of mice, suggesting an important role for LRP1 in GABAergic neurons in motor function [30,31]. However, previous studies demonstrated that reduction in motor coordination is also accompanied by increased adiposity, increased circulating insulin and leptin levels, and glucose intolerance [32,33], and crosstalk between leptin and insulin signaling [34][35][36]. Moreover, while GABAergic LRP1 deleted mice were hypoactive and obese, non-obese mice with panneuronal LRP1 deletion exhibited hyperactive characteristics [31].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies using targeted deletion of LRP1 in the forebrain of mice, suggesting an important role for LRP1 in GABAergic neurons in motor function [30,31]. However, previous studies demonstrated that reduction in motor coordination is also accompanied by increased adiposity, increased circulating insulin and leptin levels, and glucose intolerance [32,33], and crosstalk between leptin and insulin signaling [34][35][36]. Moreover, while GABAergic LRP1 deleted mice were hypoactive and obese, non-obese mice with panneuronal LRP1 deletion exhibited hyperactive characteristics [31].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies where LRP1 was generally deleted from the forebrain of mice, indicating the significant role of LRP1 in GABAergic neurons in motor function [ 36 , 37 ]. However, experimental evidence demonstrated that reduction in motor coordination is also accompanied by increased adiposity, increased circulating insulin and leptin levels, glucose intolerance [ 38 , 39 ], and crosstalk between leptin and insulin signaling [ [40] , [41] , [42] ]. Moreover, while GABAergic LRP1 deleted mice were hypoactive and obese, non-obese mice with pan-neuronal LRP1 deletion exhibited hyperactive characteristics [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…TST is widely used to assess the social behavior of animals in studies [23] , and the results of our experiments showed that autistic rats exhibited signi cant social impairment. The cognitive functions of animals are generally evaluated by learning and memory abilities, which became signi cantly worse in autistic rats in the NOR task [24] . All of the above ndings indicate that the autistic rats were successfully modeled in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Learning memory impairment in autism was evaluated using the novel object recognition (NOR) task [24] .…”
Section: Novel Object Recognition Taskmentioning
confidence: 99%